Osteomorphological features of the hind limb bones of Saiga antelope (Saiga tatarica). (26th July 2020) - Jing, Libaihe; He, Peng; Ding, Dongfang; Qu, Can; Shao, Baoping; Ma, Jizhong; Wang, Jianlin
Abstract: The intralimb indices and calcaneal linear metrics are known as the reliable predictors of locomotor adaptation in artiodactyls. The osteological features of hindlimb in adult Saiga ( Saiga tatarica ) were described, and its correlation with cursoriality and habitat adaptation was discussed. Gross anatomy data showed Saiga owned the deep acetabulum as a broad lunate surface, the large acetabular anteversion, the well‐developed ischiatic tuberosity and the prominent gluteal lines. It also presented the robust rough line and the strong gluteal tuberosity. A proximodistally elongated eminence located on the cranially distal tibia, which had not been found in goat. The tibial extensor groove was deep. The calcaneal tuberosity was robust. Digital anatomy data showed Saiga owned the higher metatarsal‐femur ratio than forest musk deer and sheep. Comparing with wild bovids and sheep, Saiga presented a transitional variation in calcaneal form. The mean greatest length of the calcaneus (GLC) and the height of the sustentacular facet (HSF) in Saiga were shorter than that in sheep and longer than that in wild bovids respectively ( F  = 587.492; F  = 10.264, p  < .05). The wild bovids had longer cubonavicular facets than the other two groups ( F  = 18.587, p  < .05). The great metatarsal–femur ratio of Saiga implied a superior cursorial ability and high conservation confronting the different habitats. The calcaneal linear metrics might shed light on lifestyle‐related functional adaptation over decades of short‐term evolution in the semi‐free range environment.